Blockchain-based dispute resolution: Insights and challenges - Yannick Gabuthy (Games, 2023)
A smart contract can be defined as a computer program, stored on a blockchain, which allows a transaction or an agreement-defined ex-ante-to be self-executed when some conditions are met, and without the need for a central authority to enforce it. Even if this new technology is very promising, it may face a challenge: the codified nature of smart contracts creates new types of disputes that require new mechanisms of dispute resolution, which are precisely based on the blockchain. The aim of this article is to analyze one of these emerging mechanisms, namely Kleros, which is a blockchain-based dispute resolution platform implying crowdsourced jurors whose incentives to make fair decisions are based on game theory. The Kleros case provides also a basis for a broader discussion on the future of the decentralized justice market.
Keywords: C72; K41; 330; blockchain; smart contracts; litigation; decentralized justice